PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN RESTORAN DâCOST PLAZA ANDALAS PADANG - Monica, Stella; Dewita Hia, Yulna; Sumarni, Sumarni (Pendidikan Ekonomi, 2014)
Â ABSTRAKÂ 1Â Issues that are examined in this study is the influence of marketing mix on customer satisfaction cost d restaurant Andalas Padang plaza. The purpose of this study was to analyze the effect of marketing mix on customer satisfaction cost d restaurant plaza andalas Padang . The methodology used in this study is the method of multiple linear regression analysis. The technique of collecting data using questionnaires , such as statements regarding the marketing mix consists of product , price , distribution and location of the restaurant customer satisfaction d costs Andalas Padang plaza. Collected through documentation related to the restaurant. First results showed that : The product does not affect the customer satisfaction restaurants Plaza Andalas Padang DCost indicated by the coefficient value of -0167 with a significant value of 0.213 > Î± = 0.05 . Second : The price does not affect the customer satisfaction restaurants Plaza Andalas Padang DCost indicated by a coefficient of 0.224 with significant value of 0.155 > Î± = 0.05. Third : The price does not affect the customer satisfaction restaurants Plaza Andalas Padang DCost indicated by the coefficient value of -0048 with a significant value of 0.793 > Î± = 0.05 . Fourth : Promotion of positive and significant effect on customer satisfaction restaurants Plaza Andalas Padang DCost indicated by a coefficient of 0.863 with significant value of 0.000 < Î± = 0.05. Fifth : Product , Price , Distribution and Location jointly influence on customer satisfaction indicated by the F - statistic of 18.873 , with a significant value of 0.000 < Î± = 5 % , and the R - squared value of 0.627 , which means by 62 , 7 % customer satisfaction is affected by the variable product , price , distribution and location while the rest is explained by other variables. From this study the authors concluded that the product , price , and distribution does not affect the customers satisfaction , whereas the effect on customer satisfaction Promotion restaurant Plaza Andalas Padang DCost , for it suggested to the Restaurant DCost for more attention to the promotion of applied management to can improve customer satisfaction restaurants Plaza Andalas Padang DCost .